Comparison of Mesh Fixation Techniques in Elective Laparoscopic Repair of Incisional Hernia-ReliaTack™ v ProTack™ (TACKoMesh) - A double-blind randomised controlled trial - Sheen, Aali J. (BMC Surg, 2018)
BACKGROUND: Minimally invasive incisional hernia repair has been established as a safe and efficient surgical option in most centres worldwide. Laparoscopic technique includes the placement of an intraperitoneal onlay mesh with fixation achieved using spiral tacks or sutures. An additional step is the closure of the fascial defect depending upon its size. Key outcomes in the evaluation of ventral abdominal hernia surgery include postoperative pain, the presence of infection, seroma formation and hernia recurrence. TACKoMESH is a randomised controlled trial that will provide important information on the laparoscopic repair of an incisional hernia; 1) with fascial closure, 2) with an IPOM mesh and 3) comparing the use of an articulating mesh-fixation device that deploys absorbable tacks with a straight-arm mesh-fixation device that deploys non-absorbable tacks. METHODS: A prospective, single-centre, double-blinded randomised trial, TACKoMESH, will establish whether the use of absorbable compared to non-absorbable tacks in adult patients undergoing elective incisional hernia repair produces a lower rate of pain both immediately and long-term. Eligible and consenting patients will be randomized to surgery with one of two tack-fixation devices and followed up for a minimum one year. Secondary outcomes to be explored include wound infection, seroma formation, hernia recurrence, length of postoperative hospital stay, reoperation rate, operation time, health related quality of life and time to return to normal daily activity. DISCUSSION: With ongoing debate around the best management of incisional hernia, continued trials that will add substance are both necessary and important. Laparoscopic techniques have become established in reducing hospital stay and rates of infection and report improvement in some patient centered outcomes whilst achieving similarly low rates of recurrence as open surgical techniques. The laparoscopic method with tack fixation has developed a reputation for its tendency to cause post-operative pain. Novel additions to technique, such as intraoperative-sutured closure of a fascial defect, and developments in surgical technology, such as the evolution of composite mesh design and mesh-fixation devices, have brought about new considerations for patient and surgeon. This study will evaluate the efficacy of several new technical considerations in the setting of elective laparoscopic incisional hernia repair. TRIAL REGISTRATION: Name of registry - ClinicalTrials.gov Registration number: NCT03434301. Retrospectively registered on 15th February 2018.